ASPECTS OF MULTI-CRITERION SELECTION OF ADMINISTRATIVE DECISIONS - Мормуль, Микола; Щитов, Дмитро; Щитов, Олександр; Рудянова, Тетяна (SWorldJournal, 2023)
The main problems of multi-criteria selection of management solutions in economic, management and technical systems are considered. The practical implementation of the multi-criteria selection of alternatives for evaluating the efficiency of enterprises w